PERKEMBANGAN MUSIK DAN BUDAYA HIP-HOP DI TIONGKOK: EKSISTENSI THE RAP OF CHINA DI TENGAH KETATNYA SENSOR - Chumairo, Matsnaa; Mutia, R. Tuty Nur (Paradigma: Jurnal Kajian Budaya, 2023)
Hip-hop culture and rap music originated from the African-American community that emerged around the 1970s in New York City. Hip-hop started to enter PRC in the 1990s and continues to grow among the younger generation. A hip-hop talent search show titled The Rap of China, released in 2017, became very popular, bringing hip-hop music and culture to the fore. Unfortunately, it must eventually face PRC government’s intervention in its development. This article discusses the influence of Chinese government's censorship policies on the development of hip-hop music and culture in China. This case study was conducted using the historical approach, with the primary data source being the recordings of The Rap of China from seasons 1 to 4. One of our most important findings is that hip-hop music and culture can survive and thrive amid the strict censorship of the PRC government.